Malignancies in HIV infection - Chandran, Rabindran; Gedam, D Sharad (International Journal of Medical Research and Review, 2015)
HIV is associated with malignancies. AIDS defining malignancies are Kaposi’s Sarcoma, B cell non- Hodgkin’s lymphoma, Primary CNS lymphoma & cervical cancer